Contemporary architects 1 : Les nouveaux maitres de l 'architecture = Zeutgenossishe architekten 1 =Hedendaagse architecten 1 =Arquitectos contemporaneos 1 = I nouvi maestri dell 'architettura =Arquitectos contemporanneos 1 = Nutida arkiteker 1 (New masters of architecture, 2012)
Each volume in this collection features the most representative works of 30 leading architects in the international arena. These studios or individual architects have been distinguished with numerous local and international awards for their innovative contributions to the world of architecture and for designing new buildings that fulfil an important cultural, political and social purpose. Their projects have become icons because of their spectacular design or the use of new construction materials. New technologies, home automation, functionality, spectacular structures and respect for the environment have earned them a place in the annals of architectural history.